Very high multiplicity physics workshops : proceedings of the VHM physics workshops, JINR, Dubna, Russia, 17-19 September 2007 - Sisaki͡an, A. N.; Manjavidze, Joseph (World Scientific, 2008)
"This proceedings volume provides a comprehensive overview of the selected reports given at the International Workships on Very High Multiplicity Physics from 2000 through 2007. These include results of original investigations dedicated to very high multiplicity processes, collective phenomena in quark gluon plasma, correlator analyses, polarization effects, and pion gas condensation, among others. The greater part of the material is devoted to basic technical aspects of the NICA/MPD project. Essential attention is paid to predictions of the multipheral model, perturbative QCD, physics of small x, and fractal analysis and statistical physics approaches to multiple production." "The book is an important reference for physicists working in elementary particle physics. It is also a suitable read for undergraduate students."--Jacket